Representation of Meaning Through the Stylistics of the Poems "Telaga", "Metamorfosa" and "Pohon Pisang" by Kusprihyanto Namma - Kristiana Rizqi Rohmah; Anis Setyawati; Nur Aini Syah (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
The purpose of this study is to analyze the three poems of Kusprihyanto Namma using stylistic studies. This research is motivated by the content of Kusprihyanto Namma’s poems which have deep meanings, especially when studied using stylistic theory. Just like the three poems of Kusprihyanto Namma “Telaga” “Metamorfosa” and “Pantai Pisang” which contain a lot of diction, style of language and imagery. The research method used is descriptive qualitative with literature study so that the time and place of research are not available. The population and sample in this study are sentences in Kusprihyanto Namma’s poems entitled “Telaga”, “Metamorfosa” and “Pantai Pisang”. The research instrument used is the theory of diction, style of language and imagery. Data collection techniques by reading and taking notes. The data analysis technique uses stylistic studies. Stylistic studies are studies that interpret words or sentences. The results of the study show that there are diction, style of language and imagery in Kusprihyanto Namma’s poems. Diction includes descriptive, connotative, and concrete words. However, not every poem by Kusprihyanto Namma contains all three of these instruments. In “Telaga,” diction, figurative language, and imagery are fully represented. In “Metamorfosa,” diction and imagery are present. Meanwhile, in “Pantai Pisang,” diction and imagery are present. Although diction, imagery, and figure of speech are not fully represented, the meaning of Kusprihyanto Namma’s three poems is very significant. Good poetry is indeed poetry that has deep meaning, especially in the aspects of diction, figurative language, and imagery.